The Creative Exploitation of Pedagogy’s Added Value in the Blogosphere to the Field of Early Childhood Education - Michael Vitoulis (Archives of Current Research International, 2017)
This article highlights the popularity of the pre-school blogosphere and examines it as part of its creative exploitation, at a theoretical level, suggesting a version of the creation of a knowledge hub in the field of early childhood education. It develops a proposal to create a knowledge hub with inspiration derived from the study of Greek-speaking blogosphere of early childhood education. It approaches the blogosphere as precursor of knowledge hub in the field of early childhood education. The article describes the characteristics of the blogosphere, while it attempts a conceptual approach of the knowledge hub. Within a creative future perspective, it presents the potential benefits for educators. Finally, it proposes a model of development of a knowledge hub for early childhood education.